1991
DOI: 10.1159/000108877
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Acute Cerebral Ischemia: PET Studies in Humans

Abstract: Using positron emission tomography (PET), the combined imaging of cerebral blood flow (CBF), cerebral blood volume (CBV), tissue oxygen tension (PtO2), oxygen extraction fraction (OEF), oxygen consumption (CMRO2) and glucose utilization (CMRglu) has allowed to demonstrate the 3 stages of hemodynamic compromise associated with acute arterial occlusion (1) autoregulation stage (hemodynamic reserve) with elevation of CBV; (2) oligemic stage (OEF reserve) with reduced CBF, elevated OEF and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…(1) The strategic location of the lesion in the thala mus, corticothalamic areas or in both hemispheres [26,[49][50][51][52][53][54], (2) Positron emission tomography (PET) and single photon emission tomography studies showed that the damaged cerebral areas were more extensive than those visualized by CT scan [55][56][57], A matched decrease in cerebral blod flow (CBF) and oxygen consumption (CMRO2) may affect the whole cerebral cortex, as well as deep structures being undetected by CT scan [55,58,59]. Different altered PET patterns of CBF and CMROt in patients with ischemic infarctions are relevant to the neu rological outcome [60], and the lowest global cerebral glu cose consumption rates were found in patients with small deep infarctions [56], On the other hand, the regional CBF was significantly lower in subjects with silent lacunar lesions, this feature probably being of some relevance in detecting significant hypoperfusions far away from the lesions [61].…”
Section: The Relationship Between Lacunar Infarcts and Dementiamentioning
confidence: 99%
“…(1) The strategic location of the lesion in the thala mus, corticothalamic areas or in both hemispheres [26,[49][50][51][52][53][54], (2) Positron emission tomography (PET) and single photon emission tomography studies showed that the damaged cerebral areas were more extensive than those visualized by CT scan [55][56][57], A matched decrease in cerebral blod flow (CBF) and oxygen consumption (CMRO2) may affect the whole cerebral cortex, as well as deep structures being undetected by CT scan [55,58,59]. Different altered PET patterns of CBF and CMROt in patients with ischemic infarctions are relevant to the neu rological outcome [60], and the lowest global cerebral glu cose consumption rates were found in patients with small deep infarctions [56], On the other hand, the regional CBF was significantly lower in subjects with silent lacunar lesions, this feature probably being of some relevance in detecting significant hypoperfusions far away from the lesions [61].…”
Section: The Relationship Between Lacunar Infarcts and Dementiamentioning
confidence: 99%
“…5,6 Positron emission tomography (PET) using 15 O identifies areas of misery perfusion in a patient with acute ischemic stroke. 7,8 18 F-fluoromisonidazole (FMISO) is a PET marker of hypoxic but viable tissue that exists in an acute ischemic area in the human brain, [9][10][11][12] and areas with uptake of the tracer reportedly are metabolically compromised tissue at risk of infarction after acute ischemic stroke. 9,10,12 The mechanism of selective retention of 2-nitroimidazoles, including FMISO, in hypoxic tissue is not clearly understood but may involve nitroreductases.…”
mentioning
confidence: 99%
“…1989; Sette et aI., 1989;Baron, 1991;Heiss et aI., 1992). These reports described the frequent occur rence of marked oxygen extraction fraction (OEF) increases in the ischemic regions within 6-48 h fol lowing onset of stroke, indicating that an oligemia!…”
mentioning
confidence: 99%